Volatile emissions of flexible polyurethane foams as a function of time - Hornyák-Mester Enikő; Mentes Dóra; Farkas László; Hatvani-Nagy Alpár Ferencz; Miklós Varga; Viskolcz Béla; Muránszky Gábor; Fiser Béla; Bela Fiser; Фішер Бейло (Elsevier, 2023)
Abstract. Growing concerns about the emissions of plastic products have caused many major changes worldwide in recent years. Legal requirements, health concerns, the expectations of customers and the global automotive industry to produce increasingly safer products have encouraged the development of new analysis methods and the intro duction of emission standards by car manufacturers. The substances responsible for volatile emissions (VOC and SVOC content) from automotive flexible polyurethane foams (e.g. car seats) were studied 1, 2, 5, 10, 20, and 30 days after production according to a slightly modified VDA 278 standard. This research helps to understand both the short-term and longer-term volatile content, thus, the emissions affecting the workers and the subsequent effects on the customer after installation of the product are also monitored. It was determined that the catalysts and surfactant used in the formulation was responsible for most of the VOC content. In light of the results, recommendation was also provided on which additives need to be replaced in order to meet industry expecta tions and the replacement of two additives (DMAEE and surfactant) was investigated. Thus, a unique approach is presented which combine the strength of analytical techniques with industrial requirements to provide safer products for the end users.
Editorial board: https://www.sciencedirect.com/journal/polymer-degradation-and-stability/about/editorial-board
Contents: https://www.sciencedirect.com/journal/polymer-degradation-and-stability/vol/216/suppl/C
Keywords: PUR; DABCO; DMAEE; Siloxanes; Volatile organic compounds; VDA 278